Innovative man-machine interface - Poo, Ce Yu (2016)
This project is about designing and constructing a game base on KinectSensor to satisfy the needs of the elderly and wheelchairbounded person. The game is created to use gesture to control a Remote Control Car. In this report will cover the methodology of creating algorithms, design of circuits and documentation. Experimental results on different settings are also presented to show which setting will be best for this project. The future plans and improvement will be shared also be the conclusion.